MTHFD2 promotes tumorigenesis and metastasis in lung adenocarcinoma by regulating AKT/GSK‐3β/β‐catenin signalling. Issue 14 (13th June 2021) - Shi, Yangfeng; Xu, Yiming; Yao, Jianchang; Yan, Chao; Su, Hua; Zhang, Xue; Chen, Enguo; Ying, Kejing
Abstract: Recent studies have demonstrated that one‐carbon metabolism plays a significant role in cancer development. Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2), a mitochondrial enzyme of one‐carbon metabolism, has been reported to be dysregulated in many cancers. However, the specific role and mechanism of MTHFD2 in lung adenocarcinoma (LUAD) still remains unclear. In this study, we evaluated the clinicopathological and prognostic values of MTHFD2 in LUAD patients. We conducted a series of functional experiments in vivo and in vitro to explore novel mechanism of MTHFD2 in LUAD. The results showed that MTHFD2 was significantly up‐regulated in LUAD tissues and predicted poor prognosis of LUAD patients. Knockdown of MTHFD2 dramatically inhibited cell proliferation and migration by blocking the cell cycle and inducing the epithelial‐mesenchymal transition (EMT). In addition, MTHFD2 knockdown suppressed LUAD growth and metastasis in cell‐derived xenografts. Mechanically, we found that MTHFD2 promoted LUAD cell growth and metastasis via AKT/GSK‐3β/β‐catenin signalling. Finally, we identified miR‐30a‐3p as a novel regulator of MTHFD2 in LUAD. Collectively, MTHFD2 plays an oncogenic role in LUAD progression and is a promising target for LUAD diagnosis and therapy.